Peran BUMDes Terhadap Pendapatan Petani Di Desa Karangsono Kecamatan Dander Kabupaten Bojonegoro - Hafif, Nur; Daryanto, Didik (Sam Ratulangi University, 2023)
This study aims to examine the management of BUMDes, examine the role of BUMDes on farmers' income, and to examine the supporting and inhibiting factors of BUMDes Mulyo Lestari. This study used qualitative research, the location and time of the research was carried out in Karangsono Village, Dander District, Bojonegoro Regency from March to June 2023. The selected informants were informants who knew the situation and could provide reliable information about the object being studied. Data collection techniques are in-depth interviews, observation, and documentation. Data analysis techniques is inductive method through providing a clear description of problem information, then interpreting them in accordance with the results of research conducted based on theoretical support related to the research object, while data validation techniques use triangulation, data reduction, data collection, and drawing conclusions. The results of this study indicate that the role of BUMDes in the income of farmers in Karangsono village has helped farmers earn a decent income, it's just that sustainable management is still not optimal. BUMDes management is already running in accordance with organizational management rules, but the functions in organizing, activating and supervising are still not optimal. The supporting factors for BUMDes are the existence of capital participation from the village government and high natural resources, while the low quality of human resources and the lack of community involvement in achieving BUMDes goals, are obstacles for BUMDes.